Comparative Responsiveness of the PROMIS Pain Interference Short Forms, Brief Pain Inventory, PEG, and SF-36 Bodily Pain Subscale. Issue 4 (April 2016) - Kean, Jacob; Monahan, Patrick O.; Kroenke, Kurt; Wu, Jingwei; Yu, Zhangsheng; Stump, Tim E.; Krebs, Erin E.
Abstract : Purpose: To compare the sensitivity to change and the responsiveness to intervention of the PROMIS Pain Interference short forms, Brief Pain Inventory (BPI), 3-item PEG scale, and SF-36 Bodily Pain subscale in a sample of patients with persistent musculoskeletal pain of moderate severity. Methods: Standardized response means, standardized effect sizes, and receiver operating curve analyses were used to assess change between baseline and 3-month assessments in 250 participants who participated in a randomized clinical effectiveness trial of collaborative telecare management for moderate to severe and persistent musculoskeletal pain. Results: The BPI, PEG, and SF-36 Bodily Pain measures were more sensitive to patient-reported global change than the PROMIS Pain Interference short forms, especially for the clinically improved group, for which the change detected by the PROMIS short forms was not statistically significant. The BPI was more responsive to the clinical intervention than the SF-36 Bodily Pain and PROMIS Pain Interference measures. Post hoc analyses exploring these findings did not suggest that differences in content or rating scale structure (number of response options or anchoring language) adequately explained the observed differences in the detection of change. Conclusions: In this clinical trial, the BPI and PEG measures were better able to detect change than the SF-36 Bodily Pain and PROMIS Pain Interference measures.